A rare case of malignant transformation of condylar osteochondroma: Diagnosis and treatment - Tingkun Hou; Fang Nie (Radiology Case Reports, 2025)
Condylar osteochondroma with malignant transformation into well-differentiated chondrosarcoma is exceptionally rare. We report a 43-year-old Chinese female presenting with facial asymmetry and a firm left temporomandibular joint mass. Imaging suggested a benign lesion, but ultrasound-guided biopsy and histopathology confirmed focal malignant transformation, later validated by S-100/SOX-9 positivity following surgical resection. This case underscores the diagnostic challenges of chondrosarcoma arising from osteochondroma and highlights the critical role of histopathological confirmation in guiding management. Early detection and intervention are essential to mitigate complications, emphasizing the need for further research into this rare entity.